Slicing Cuts on Food Materials Using Robotic-Controlled Razor Blade - Debao Zhou; Gary McMurray (Modelling and Simulation in Engineering)
Cutting operations using blades can arise in a number of industries, for example, food processing industry, in which cheese, fruit and vegetable, even meat, are involved. Certain questions will rise during these works, such as “why pressing-and-slicing cuts use less force than pressing-only cuts” and “how is the influence of the blade cutting-edge on force”. To answer these questions, this research developed a mathematical expression of the cutting stress tensor. Based on the analysis of the stress tensor on the contact surface, the influence of the blade edge-shape and slicing angle on the resultant cutting force were formulated and discussed. These formulations were further verified using experimental results by robotic cutting of potatoes. Through studying the change of the cutting force, the optimal slicing angle can be obtained in terms of maximum feeding distance and minimum cutting force. Based on the blade sharpness properties and the specific materials, the required cutting force can be predicted. These formulation and experimental results explained the basic theory of blade cutting fracture and further provided the support to optimize the cutting mechanism design and to develop the force control algorithms for the automation of blade cutting operations.